On estimation of population mean based on two measurements. Issue 21 (2nd November 2017) - Nadarajah, Saralees; Li, Rui; Roozegar, Rasool; Dolati, Ali
ABSTRACT: There are many estimators for population mean: arithmetic mean, median, root mean square, geometric mean, harmonic mean, and so forth. Which one is the best? Here, we answer this question given two measurements from a uniform distribution.